1996
DOI: 10.1104/pp.110.1.155
|View full text |Cite
|
Sign up to set email alerts
|

Phytochrome A Regulates Red-Light Induction of Phototropic Enhancement in Arabidopsis

Abstract: Phytochrome A (phyA) and phytochrome B photoreceptors have distinct roles in the regulation of plant growth and development. Studies using specific photomorphogenic mutants and transgenic plants overexpressing phytochrome have supported an evolving picture in which phyA and phytochrome B are responsive to continuous far-red and red light, respectively. Photomorphogenic mutants of Arabidopsis thaliana that had been selected for their inability to respond to continuous irradiance conditions were tested for their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
102
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(111 citation statements)
references
References 35 publications
(40 reference statements)
9
102
0
Order By: Relevance
“…Within the limits of stability phy-1 is capable of mediating the effect of a FR-reversible induction by R-pulse irradiation. This is similar to recent results obtained with phyAand phyB-deficient Arabidopsis mutants (Parks et al, 1996), although FR reversion of phyA action has not been shown in these experiments. The disappearance of phy-1 exposes the action of the light-stable phy-s, which is either inactive or overcompensated in the presence of phy-I.…”
Section: Interpretation Of Growth and Mt-reorientation Datasupporting
confidence: 82%
See 1 more Smart Citation
“…Within the limits of stability phy-1 is capable of mediating the effect of a FR-reversible induction by R-pulse irradiation. This is similar to recent results obtained with phyAand phyB-deficient Arabidopsis mutants (Parks et al, 1996), although FR reversion of phyA action has not been shown in these experiments. The disappearance of phy-1 exposes the action of the light-stable phy-s, which is either inactive or overcompensated in the presence of phy-I.…”
Section: Interpretation Of Growth and Mt-reorientation Datasupporting
confidence: 82%
“…Moreover, there are indications for a response-specificity in the action of the two phytochromes. For instance, the R-induced enhancement of phototropism in Arabidopsis seedlings is specifically mediated by phyA (Parks et al, 1996).…”
Section: A Physiological Approachmentioning
confidence: 99%
“…In studies of coleoptile phototropism and gravitropism in seedlings grown on clinostats, it was shown that decreased negative gravitropism could lead to increased phototropic curvatures (Shen-Miller & Gordan 1967;Nick & Schafer 1988). Because phytochrome activation by R enhances the development of phototropic curvature and can alter gravitropism, it has been suggested that R-induced enhancement of phototropism might be attributed in part to a change in gravitropism (Parks et al 1996). In Arabidopsis, the effect of R on gravitropism is consistent with this model, but in several other plants that display R-induced enhancement of phototropism, R treattnent resulted in a more robust gravitropic response (Wilkins & Goldstnith 1964;Woitzik & Mohr 1988).…”
Section: Gravitropism and Phototropismmentioning
confidence: 99%
“…A red-light pulse given prior to the blue-light phototropic stimulus causes a large increase in seedling curvature over the most effective range of blue-light fluences in the wild type but not in ih& phyA null mutants (Pai'ks, Quail & Hangarter 1996).…”
Section: Sensitization To Biue-iight Phototropic Signaismentioning
confidence: 99%